Composição bioquímica do plasma seminal de caprinos sem padrão racial definido (SPRD) em clima tropical úmido - Catunda, Ana Glaudia Vasconcelos (2007)
Goat seminal plasma (SP) biochemical composition observed to very in high latitudes due to seasonality. In low latitudes this variation has been attributed only to the low nutritional value of diets in the dry period. The aims of this study were to evaluate the occurrence of variation in the SP biochemical composition of SPRD goats breed intensively in the State of Ceará, Brazil. The experiment was carried out in the facilities of Dep. of Zootecnia of the Federal University of Ceará - UFC. Twenty male SPRD goats were used, they were fed according to NRC/goats (1981). Ejaculated were collected weekly in artificial vagina and eletroejaculador, and evaluated, measure, centrifuged and separated the SP (sobreswing) from the cells spermatic (precipitate), being stored in eppendorff tubes at -18°C, during one year (Sep/2005 the Aug/2006). For analyses purpose weekly sample were mixed to constitute a monthly individual pool, from which were evaluated the concentrations of Ca, P, Mg, PTt, CA and fructose. Significant variation was observed (p <0,05) in the biochemical composition of the SP among the periods of the year, registering the highest levels of biochemical parameters in the rainy period. The individual variation was significant (p <0,01), only having significant interaction animal/period to the fructose (p <0,05). The study of correlations showed significant associations (p <0,0001) among PTt, CA and fructose, among the ejaculate volume and of SP with the components, and of temperature, humidity, precipitation and ITU with the biochemical parameters of the SP. It is concluded that fructose is a good biochemical parameter for the study of seminal quality. However, more studies are necessary to identify the causes of this variation, and to better understand the role of the fructose, citric acid and total proteins in the metabolism spermatic